China looks to ASEAN for closer ties, freer trade, and more harmonious relations: a Commentary - Feng, Haiying; Wu, Jingji; Squires, Victor R. (Archives of Business Research, 2021)
This paper is in three main parts. Firstly, we summarize key features of the history of trade relationships between the People’s Republic of China (PRC) and the Association of South East Asian countries (ASEAN). This includes a brief examination of the different visions held by ASEAN and PRC and the implications for the various trade partners. In the second part we turn our focus to the Guangxi Zhuang Autonomous Region (GAZR) that is on the shores of the South China Sea and a key region being developed as the Beibu Gulf Economic Rim. The port city of Qinzhou is the nearest deep-water port to the ASEAN countries like Malaysia, Vietnam, Philippines etc and lies at the eastern end of the Southern Transport Corridor (STC) that links Lanzhou on the Yellow River in NW China, to the coast. Finally, we present a cameo on Qinzhou’s Free Trade Port Areas and their role in the ASEAN–China Free Trade Agreement (ACFTA).